Material/Spiritual Seeding? Problematising Religion and Gullibility in Zimbabwe - Muyambo, Tenson M. (Alternation - Interdisciplinary Journal for the Study of the Arts and Humanities in Southern Africa, 2020)
The media in Southern Africa is inundated by ‘strange’ events that happen in the church. The events range from congregants who are asked to eat grass; who allow a ‘Man of God’ to literally walk on their stomachs while lying prostrate on the ground; those who ‘generously’ donate in church when they do not have enough to eat at home, to those who are raped under the banner of healing. The actions are ordinarily understood by onlookers as either unacceptable levels of tolerance or signs of hopelessness by the congregants. The tendency by onlookers is to quickly pass judgement without an attempt to understand what is going on from the believer’s perspective. This chapter utilises in-depth interviews with congregants hoping to understand why some of them behave the way they do. This is done in order to understand them before passing uninformed comments. The chapter found out that the believers see nothing absurd in their behaviour. Whose judgement then matters? The onlookers’ or the congregants’? The chapter argues that if we use the phenomenology of religion lens, seeding in the church is not religious gullibility for believers but for scholars/researchers it is religious gullibility that violates certain fundamental human rights.
free